Stress as a Mediator of Work Engagement and Learning Organization on Employees’ Work Performance - Manurung, Antonius Dieben Robinson (Kuras Institute, 2024)
This study aims to determine and analyze the effect of work engagement and learning organizations simultaneously on work performance through employee stress at Pupuk Kalimantan Timur Corporation. Research sampling with purposive sampling technique, namely, the sample is carried out with the requirements set by the researcher totaling 1,370 employees from various work departments, both at the center and at the branch. This research uses a quantitative approach with Structural Equation Modeling (SEM) - Smart PLS. The results of the study are known how important work performance is as a critical indicator of success for both employees and the company, the importance of understanding stress from concept to application, especially related to how to manage stress, as well as the implementation of work engagement and learning organizations as concepts that affect work performance with stress as a mediator.